2011
DOI: 10.21608/jfds.2011.81969
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding on Beef Patties Fortifited With Mushroom on Serum Lipids Profile and Liver Enzymes of Hypercholesterolemic Rats

Abstract: The investigation was carried out to study the effects of feeding hypercholesterolemic rats on 35% beef patties fortified with 0, 4, 8 and 12% oyster dried mushroom on blood serum lipids profile and liver enzymes comparing with feeding on diets containing 8% dried mushroom and 8% defatted soy flour. The results showed that all diets had hypercholesterolemic lowering effect after 30 days comparing to 15 days. Moreover, group fed on 35 % beef patty fortified with 12% dried mushroom had the highest reduction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…The lowest HDL -c was found to be ( 57.35 mg / dI) in control positive. These results are in agreement with those of EL-Refai et al ., (2011b), who reported that beef patties fortified with mushroom had high hypercholestrolemic lowering effect on TC, TG and LDL-c .…”
Section: Serum Lipidsupporting
confidence: 94%
“…The lowest HDL -c was found to be ( 57.35 mg / dI) in control positive. These results are in agreement with those of EL-Refai et al ., (2011b), who reported that beef patties fortified with mushroom had high hypercholestrolemic lowering effect on TC, TG and LDL-c .…”
Section: Serum Lipidsupporting
confidence: 94%
“…and distinct aroma(El-Refai et al, 2014). Therefore, the addition of over 12% oyster mushroom might attribute to improving the sensory properties of analog burger patties by reducing the off-flavor of soy materials Based on the results, at the level of 12% oyster mushroom contents in FFS and ISP-based, especially in FFS-based analog burger patties could be improved the organoleptic properties with texture, juiciness, taste, and overall acceptability…”
mentioning
confidence: 94%